Occurrence of Salmonella in Fresh Foods Sold in the City of Nampula, Northern Mozambique - Almeida Abudo Leite Machamba; Celso Raul Silambo Chaves; Laura Amisse; Brígida Macaza; Cecília Boaventura; Isac Joaquim Presse; Acácio Salamandane (Journal of Food Quality)
Salmonellosis, an infectious disease caused by the Salmonella species, encompasses a broad spectrum of clinical manifestations, ranging from mild self-limiting gastroenteritis to severe systemic infections. It affects millions of people annually, causing immense morbidity and economic losses worldwide. This study aims to evaluate the occurrence of Salmonella in water and raw foods, focusing on meat, fish, shellfish, and vegetables consumed in the city of Nampula, north of Mozambique. A total of 81 samples of meat, fish and shellfish, vegetables, and water were collected from nine of the ten municipal markets in Nampula City. Salmonella detections were performed according to ISO 6579-1. A chi-square test was performed in the Python programming language to detect associations between positive samples and market localization. The results showed a high frequency of Salmonella. From the total sample, 38.5% were Salmonella positive. Fresh vegetables were the most contaminated samples, followed by fish, shellfish, raw meat, and water. The outcomes of this study did not find an association between the sample collection location and the test results for Salmonella. In this study, serovars of Salmonella were not identified which hinders the association of Salmonella occurrence with diseases. Consequently, we propose that the next study should focus on detecting the serotypes of Salmonella strains.